25 Family caregiver socio-economic status, access to palliative care and patients' place of death: a health survey for england study. Issue 3 (1st September 2017) - Johnson, Miriam; Allgar, Victoria; Chen, Hong; Dunn, Laurie; Macleod, Una; Currow, David
Abstract : Background: The personal impact is considerable for family caregivers at the end-of-life. Aims: To i) describe family caregivers at the end-of-life, ii) those willing to repeat this role under similar circumstances; iii) investigate associations between caregivers' household income, patients' access to palliative care services (PCS) and place of patients' death. Methods: End-of-life caregiver questions in the Health Survey for England: had someone close to them died of a terminal illness within past 5 years?; intensity of care?; PCS accessed?; place of death?; willingness to care again?. Associations were explored using univariable analyses and multiple logistic regression. Results: 2167/8861 (25%) respondents had someone close die; 645/8861 (7.3%) provided personal care ( caregivers ). Younger caregiver age (≤65; OR 2.79; 95% CI 1.36, 5.74) and use of PCS (OR: 1.95, 95% CI: 1.09, 3.48) were associated with willingness to caregive again. 55% of decedents accessed PCS. PCS access reduced hospital (p<0.001), and increased home (p<0.001) deaths. Overall, respondents' income (adjusted for PCS) was unrelated to decedents' place of death but those with the most affluent caregivers were least likely to die at home (p=0.069). Conclusions: Most who have provided end-of-life care for someone close would be willing to provide care again; more likely for younger caregivers and when PCS was accessed. PCS access was associated with fewer hospital deaths and more home deaths. Decedents with more affluent caregivers were the least likely to die at home. Such caregivers are likely to be powerful patient advocates; ensuring correct understanding of goals of care is important.